Spaces of public use: A new sociogeographic reality of territorial marginality in the periphery (Contextos: Estudios de Humanidades y Ciencias Sociales, 2018)
Based on an undergraduate research in a sector of the periphery of the Viña del Mar, in the region of Valparaíso, we observe and reaffirm the importance of the processes of territorial marginality, which is exemplified in this case by the complex reality of the enclave of Villa Arauco. Therefore, the sociogeography aims to approach the problem of the use and misuse of public spaces, which will allow us to know, even if only partially, the behavioral factors, the stimuli and the high degree of postponement and vulnerability that these sectors project, consolidating the complexity and the harmfulness of these spaces in the development of social malignity, visualizing the need to know the geosocial problems, which involve these neighborhoods. There the detriment and the alienation, signs of negativity, are accentuated, despite the changes of current society, and continue to occur and stigmatize these neighborhoods.